2003
DOI: 10.1088/0957-4484/14/3/102
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a bundle of 4 Å single-walled carbon nanotubes

Abstract: We report a high-resolution transmission electron microscope image showing a thick bundle composed of around a thousand very thin (∼4 Å) carbon nanotubes. The deposit containing the bundle was synthesized using the vertical electric-arc process. Such thin nanotubes should correspond to (4, 2), (3, 3) or (5, 0) structures which, to date, have only been produced confined in zeolite structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Theoretical calculations based on energetic considerations have shown that a free-standing SWNT with a diameter of 0.4 nm is already marginal in stability, , which means that SWNTs with diameters smaller than 0.4 nm may not survive alone without the spatial confinement of outer walls. In fact, experimental observation has proven that ultrasmall SWNTs with diameters around 0.4 nm exist as an inner core of multiwall carbon nanotubes (MWNTs) or exist in the nanosize channels of porous materials. In 2004, Zhao et al further observed that the smallest possible SWNT with a diameter of 0.3 nm can be grown inside MWNTs, which was predicted to be of the (2,2) armchair symmetry by density functional calculations. Controversially, the (2,2) tube was predicted to be semiconducting or metallic by two different first principles calculations.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Theoretical calculations based on energetic considerations have shown that a free-standing SWNT with a diameter of 0.4 nm is already marginal in stability, , which means that SWNTs with diameters smaller than 0.4 nm may not survive alone without the spatial confinement of outer walls. In fact, experimental observation has proven that ultrasmall SWNTs with diameters around 0.4 nm exist as an inner core of multiwall carbon nanotubes (MWNTs) or exist in the nanosize channels of porous materials. In 2004, Zhao et al further observed that the smallest possible SWNT with a diameter of 0.3 nm can be grown inside MWNTs, which was predicted to be of the (2,2) armchair symmetry by density functional calculations. Controversially, the (2,2) tube was predicted to be semiconducting or metallic by two different first principles calculations.…”
mentioning
confidence: 99%
“…It is reported that the many-body effects including the self-energies and excitonic binding energies result in a larger band gap for the semiconducting SWNTs than that obtained by the local density approximation; thus, the doping level for gap closing predicted in the present work might vary somewhat from the present values. On the other hand, usually, the ultrasmall SWNTs exist as an inner core of MWNTs or exist in the nanosize channels of porous materials. Thus, environmental effects also need to be involved to precisely describe the electronic properties of the smallest (2,2) tube. Previous experimental and theoretical studies indicate that the gap size of a semiconducting SWNT in the surrounding materials around the tube decreases due to the dielectric screening effect, resulting from a decrease in both the quasi-particle excitation energies and many-body effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations